2017
DOI: 10.1007/s40974-017-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of seasonal storage for community-level energy systems: status and needs

Abstract: The status and needs relating to the optimal design of community seasonal energy storage are reported. Thermal energy storage research has often focused on technology development and integration into buildings, but little emphasis has been placed on the most advantageous use of thermal storage in community energy systems. Depending on the composition and characteristics of a community, the most appropriate community thermal storage may differ from that for a single building. District energy systems usually lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 107 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Still others carried out life-cycle cost analyses of integrating seasonal storage into district heating networks by taking into account economic and environmental boundary conditions (e.g. [20,40]), or by focussing on the most appropriate type, scale and number [41] or size of the storage [42] for optimal integration into community energy systems. Renewable energy production of both electricity and heat appears feasible in the Arctic, but energy storage remains the most important and common problem among all intermittent renewable resources.…”
Section: Introductionmentioning
confidence: 99%
“…Still others carried out life-cycle cost analyses of integrating seasonal storage into district heating networks by taking into account economic and environmental boundary conditions (e.g. [20,40]), or by focussing on the most appropriate type, scale and number [41] or size of the storage [42] for optimal integration into community energy systems. Renewable energy production of both electricity and heat appears feasible in the Arctic, but energy storage remains the most important and common problem among all intermittent renewable resources.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal storage, in a seasonal model, was examined for a community level system also by Koohi S. et al Their novel study concluded in underlining the necessity of seasonal storage for the advancement of the energy transition. In this study, it was stated that in many community cases, a mix of long and short term storage solutions might be investigated as the technology is still under improvement [26]. The same conclusion was reached by Acheilas I. et al, who assessed a decision support tool for district heating from geothermal sources in existing cities.…”
Section: Introductionmentioning
confidence: 53%
“…Field of Study/Main Contributions [22,23,27,30,31,[43][44][45][46][47][48][49][50] • District heating/multigeneration systems/local energy [24,29,[51][52][53][54][55][56] • District heating/bidirectional heat grids [28,47,57,58] • Heating pipeline/distributed energy resources [12,25,26,[59][60][61] • Seasonal storage/multi-energy/combined electrical thermal…”
Section: Referencesmentioning
confidence: 99%
“…DES can take the form of either electrical or thermal energy storage. Thermal storage could be particularly useful to address the challenge of decarbonising heating and cooling [16], however in this work we focus on electricity storage and its ability to support the integration of distributed renewable energy sources in towns and cities. In the UK, the market for domestic-scale electricity storage technologies has developed rapidly over the last few years.…”
Section: Des Technologies and Urban Energy Systemsmentioning
confidence: 99%